The Role of Digital Financial Literacy and Organizational Cultureon Employee Performance with Financial Information systemas a Mediation variable, the Locus in Kodam IV/Diponegoro - Trisna Wulandari; Fulien Surjana (Proceeding of The International Conference on Business and Economics, 2026)
This study aims to analyze the influence of Digital Financial Literacy and Organizational Culture on Employee Performance with Financial Information Systems as a mediating variable in Kodam IV/Diponegoro. Using an explanatory quantitative approach, data was collected through a survey of TNI and civil servant personnel who handle financial administration (purposive sampling) and analyzed using SmartPLS. The test results show that Digital Financial Literacy has a positive and significant effect directly on employee performance. On the other hand, Organizational Culture does not have a significant direct effect on performance, but has been proven to have a positive and significant impact on the effectiveness of the Financial Information System. The key findings of this study confirm the strategic position of the Financial Information System which functions as a full mediator for the Organizational Culture in improving performance, as well as being the strongest determinant factor. The implications of this study suggest a priority on strengthening the reliability of the system and the digital  competence of personnel in order to realize transparent and accountable defense governance.